BS EN IEC 62626-1. Low-voltage switchgear and controlgear enclosed equipment. Part 1. Enclosed switch-disconnectors outside the scope of IEC 60947-3 to provide isolation during repair and maintenance work (10th June 2022) - British Standards Institution,
No abstract available